(untitled) (Eurasian Scientific Herald, 2024)
In this article, the author discusses the onomasiological perspectives of the psychological terminology system in French. It is designed to uncover how concepts are enumerated and classified within the psychological framework and to study the principles that govern the terminological system. Based on the analysis of the terminology, the study aims to reveal the relationship between language, culture, and knowledge of the psyche in French. Combining materials from dictionaries, academic publications, and professional literature, the research analyzes naming conventions, the use of metaphors, and cultural references. The majority of the terms belong to the cognitive category, highlighting the focus on mental processes, while affective, behavioral, and developmental terms reflect concerns with emotional states, actions, and development throughout the life cycle. Bodily, mechanical, and spatial metaphors serve as systematic tools, with evident Freudian loanwords like “inconscient” (unconscious). Comparison with English terms reveals specific linguistic and cultural features that are distinct from those of other countries. This research also reveals that the terminology of psychological language in French is complex; it requires an understanding of metaphor and culture. The findings have practical implications for psycholinguistic concerns, as well as benefiting cross-cultural communication and education in psychology